3 - Embauche d’une analyse de la question agraire en Ouganda - Mahmood Mamdani (Africa Development, 1986)
The paper provides an analysis of the agrarian question in Ug The starting point of the analysis is the two-fold character of peasant exploitation, the basis of a two-fold capital accumulation process the countryside, from below and above, one developed relatively spontaneously through existing commodity relations, the other the result of an organised state connection, necessarily requiring a complement of extra-economic coercion, i.e. forced labour, forced land enclosures, forced contributions, forced crops, forced sales - all these amount to a systematic devaluation of labour and its products. Neither the persistently narrow home market, nor the continued function of export-import as the axis of the development that does take place, can be understood without grasping this elementary fact. Unequal relations in the countryside can be divided into two. To the extent that they rely on extra-economic coercion for their reproduction, as is characteristic of practices associated with the comprador/bureaucrat bourgeoisie and landlordism, they have turned into so many shackles on peasant productivity. To the extent that their reproduction is free of extra-economic coercion, as is characteristic of rich peasant and village capitalist exploitation, they contain the potential of enhancing peasant productivity. In practice, market relations are intertwined with economic coercion and the relations between village capitalists and comprador/bureaucrat bourgeoise reflect a mixture of cooperation and competition. While market relations (though unequal) are in theory fully compatible with democratic freedoms for the peasantry, the same cannot be said of practices connected with extra-economic coercion. Where direct compulsion is an integral part of production relations that define the life activity of the vast majority, no consistent democracy is possible so far as state affairs are concerned. In such a situation, direct force becomes very much a part of relations between the exploiters and the exploited, and not simply between the rulers and the ruled. Political power is a part of the process of surplus labour extraction from direct producers. It is itself an economic force, and thus marks the character of the state power that stabilises basic relations in society. In such situations, even if central state power may be legitimated through formal democratic practices like multi-party competition through regular elections, state structures in the countryside do not allow for any democratic forms of control. Neither the administrative hierarchy of chiefs, nor the judicial hierarchy of courts, nor the various District Land Committees, allow for popular intervention in their functioning. These organs are tied up with the regime of labour controls and reproduced through extra-economic coercion. In this context, the democratic struggle is confined to no more than a narrow demand for a multi-party system and free-and- fair elections. Hence, its significance is immediately confined to only those classes already free of extra-economic coercion. This is why a liberaldemocratic reform in the case of Uganda can only be a minority reform, of meaning to the bourgeoisie and the middle classes, and at most to the working class. What is needed is a much broader and popular conception of democracy, whose kernel must be the emancipation of the peasantry, the majority of society, from all forms of extra- economic coercion. The pre-requisite for such a sweeping political reform is no less than a change in the production relations of society. It is tantamount to a social transformation. It is not being suggested that an end to the practices of extra-economic coercion will automatically bring in its wake a flowering of popular democracy. While the former is a necessary condition for the latter, it is no way a sufficient condition. Democratic freedoms have never come about as a logical consequence of a free market, they have always had to be won through popular struggle. As the peasantry embody various contradictory combination of labour and property, they are incapable of evolving autonomously a consistent agrarian program, either from the point of view of labour or of capital. A consistent program for the emancipation of the peasantry as part of the labouring masses can only come from that section of the labouring people - the working class - which is itself emancipated from private property in production. The peasantry is necessarily led by either the bourgeoisie or the working class. In the absence of this realisation, it is not possible to counter the present mobilization of the peasantr